2022
DOI: 10.5535/arm.22058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Frequency Cerebellar Repetitive Transcranial Magnetic Stimulation on Balance Impairment in Patients With Cerebral Infarction

Abstract: Objective To investigate the effect of low frequency cerebellar repetitive transcranial magnetic stimulation (rTMS) on balance impairment in patients with cerebral infarction.Methods Thirty-two patients were randomly divided into two groups: rTMS group (n=16) and control (n=16). In the rTMS group, treatment was performed five times per week for 2 weeks (10 sessions), and in the control group, a sham coil was used with the sound and sensation of scalp similar to the rTMS coil. Patients in both groups underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 31 publications
0
21
0
Order By: Relevance
“…After reviewing all relevant outcome data of included studies, 1 study’s data [ 22 ] could be used directly, 10 studies’ data [ 21 , 24 , 25 , 27 – 33 ] were calculated by the formula in the data synthesis and analysis section, 2 studies’ data [ 20 , 26 ] were obtained through GetData software.10 studies only assessed the post-intervention effects of cerebellar TMS on balance capacity and/or ADL. 3 studies assessed both the post-intervention and follow-up effects of cerebellar TMS on balance capacity and/or ADL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After reviewing all relevant outcome data of included studies, 1 study’s data [ 22 ] could be used directly, 10 studies’ data [ 21 , 24 , 25 , 27 – 33 ] were calculated by the formula in the data synthesis and analysis section, 2 studies’ data [ 20 , 26 ] were obtained through GetData software.10 studies only assessed the post-intervention effects of cerebellar TMS on balance capacity and/or ADL. 3 studies assessed both the post-intervention and follow-up effects of cerebellar TMS on balance capacity and/or ADL.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies [ 21 , 25 , 26 , 28 , 30 – 33 ] with 357 stroke participants were pooled to estimate the overall effect of cerebellar TMS on BBS score. The pooled results from 8 studies with 357 participants showed that cerebellar TMS could significantly improve the post-intervention BBS score (MD = 4.24, 95%CI = 2.19 to 6.29, P < 0.00001; heterogeneity, I 2 = 74%, P = 0.0003; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A small number of clinical trials have demonstrated that repetitive Transcranial Magnetic Stimulation (rTMS) has some e cacy for reducing symptom burden in patients with cerebellar ataxia with differing etiologies, using varying treatment protocols [3]. In studies exploring post-stroke syndromes speci cally, rTMS using 1 Hz stimulation targeting the ipsilateral cerebellar hemisphere has been shown to signi cantly improve ataxia as measured by the 10-meter walk test (10MWT), Berg Balance Scale (BBS), or Timed Up and Go test (TUG) [4][5][6]. However, no data thus far have demonstrated improvement with rTMS treatment for bilateral post-stoke cerebellar ataxia.…”
Section: Introductionmentioning
confidence: 99%